Optic neuropathy as an early manifestation of granulomatosis with polyangiitis: a case report and literature review - Yukang Kim; Tonghoon Woo; Sun-Uk Lee; Sun-Uk Lee; Euyhyun Park; Euyhyun Park; Hyun-Jin Shin; Jongmin Sim; Gerard Jounghyun Kim; Ji-Soo Kim; Ji-Soo Kim (Frontiers in Medicine)
IntroductionOphthalmic involvement occurs in up to 40% of patients with granulomatosis with polyangiitis (GPA), usually confined to the anterior segment. Herein, we describe patients presenting with optic neuropathy as an early manifestation of GPA, without other signs of ocular or adnexa involvement.MethodsWe report a case of isolated optic neuropathy without other ocular or adnexal involvement and examine the reported clinical features of 17 additional patients through a literature review. We analyzed clinical characteristics and neuro-ophthalmological findings and discuss the clinical implications for the early detection of GPA-associated optic neuropathy.ResultsAmong the 17 patients, 10 had optic neuropathy confined to one eye, three exhibited simultaneous bilateral optic neuropathies at initial presentation, and four had unilateral involvement initially; however, the fellow eye was subsequently affected during follow-up. Nine patients had optic neuropathy as the first clinical presentation and no prior diagnosis of GPA (9/17, 53%). Among the 21 eyes (15 patients, excluding two without descriptions), disc edema was observed in five eyes (24%). Visual impairment was often profound; the measurements of 23 affected eyes at the initial presentation showed that the patient’s acuity was to count fingers or worse (14/23, 61%). The final visual outcome was often poor, with significant visual recovery in only eight eyes (8/23, 35%). Other constitutional symptoms or systemic involvements were found in most patients (15/16, 94%), mostly affecting the lung (n = 10), sinus (n = 9), and pachymeninges (n = 8). Furthermore, 88% of the patients (15/17) showed positive results on antineutrophil cytoplastic antibody. Elevated CRP (n = 6) or ESR (n = 5) was found in 56% of cases.DiscussionOur case and literature review indicates that optic neuropathy can present in the context of systemic inflammation of GPA, without any other signs of ocular or orbital involvement. Catching other clinical, imaging, and laboratory signs of systemic inflammation is important in cases of GPA-associated optic neuropathy with atypical presentations.